Proceedings of the Conference on Computer Support for Collaborative Learning Foundations for a CSCL Community - CSCL '02 2002
DOI: 10.3115/1658616.1658713
|View full text |Cite
|
Sign up to set email alerts
|

Using pedagogical agents to support collaborative distance learning

Abstract: In this paper, we describe an animated pedagogical agent that assists the interaction among students in a virtual class within a collaborative communication tool, either on-line or not, motivating them, correcting wrong ideas and providing new information. This guiding agent, which we call Collaboration Agent, will consider not only the cognitive capabilities of students, but also social and affective ones; this becomes a more qualitative mechanism for collaboration among students and learning. The considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…Several studies found that overhearing dialogue between a virtual tutor and a virtual tutee in virtual tutoring sessions has positive effects on observer students, such as students asking significantly more deep-level reasoning questions (Craig et al, 2000) and producing more relevant propositions in free recall questions (Driscoll et al, 2005). The positive effect of conversational/dialogue style is not only limited to improvement in retention and transfer, but also on learners' perceived difficulty, friendliness, helpfulness, and physical presence (Jaques et al, 2002).…”
Section: Learning By Observing Pedagogical Agentsmentioning
confidence: 99%
“…Several studies found that overhearing dialogue between a virtual tutor and a virtual tutee in virtual tutoring sessions has positive effects on observer students, such as students asking significantly more deep-level reasoning questions (Craig et al, 2000) and producing more relevant propositions in free recall questions (Driscoll et al, 2005). The positive effect of conversational/dialogue style is not only limited to improvement in retention and transfer, but also on learners' perceived difficulty, friendliness, helpfulness, and physical presence (Jaques et al, 2002).…”
Section: Learning By Observing Pedagogical Agentsmentioning
confidence: 99%
“…From a Pedagogical point of view, a PA is defined as an educational system that has learning strategies and that is formed by Intelligent Agents . From a software engineering point of view, agents have the advantages of modularity and flexibility (Jaques et al, 2002). Consequently, over the last several years there has been significant interest in the ITS research community for applying intelligent agents in design and deployment of ITSs (Devedzic and Harrer, 2005).…”
Section: The Generalized Pedagogical Agentmentioning
confidence: 99%
“…Other research has advocated that agent-human communication has the potential to establish emotional and social bonds with the student, a feature that can facilitate learning [14] and reduce the feelings of isolation that is common in distance learning settings [15], [16].…”
Section: Conversational Agentsmentioning
confidence: 99%